On the Impact of State Anti-inflation Policy on the Level of Poverty in Russia and Other Countries - N. M. Goreeva; L. N. Demidova; S. I. Chernyaev (Управленческие науки, 2018)
The article deals with nominal and real inflation, both in the whole country and in various sectors of Russia, including individual product groups, and identifies the main trends of inflation processes. The authors made an attempt to assess the impact of anti-inflationary measures taken in different countries on the level of social stratification of the population using nonparametric criteria. The results of the study clearly demonstrate that the use of monetary policy measures to control inflation in different countries does not reduce the proportion of the population with incomes below the subsistence level. Economic factors are not the only drivers of the human capital development and the rise of living standards. Therefore, institutional reforms must have not only a general economic effect but also the effect of social utility. The aim of the study is to identify and quantify the impact of inflation policies on human development in developed and developing countries. To achieve this goal, the work has set and solved the following tasks: real and nominal inflation rates in Russia as a whole for the past 6 years have been assessed; consumer inflation rates for individual commodity groups have been estimated; the use of nonparametric methods of assessing the impact of anti — inflationary policies on the proportion of the population with incomes below the subsistence level has been proposed and tested. The methodological basis of this article comprises economic and statistical methods of analysis, including the use of nonparametric methods and criteria for assessing non-quantitative indicators in small samples, methods of generalizing indicators, and comparison methods. The work analyzes the relationship between the GDP deflator index and the poverty level using the 2 χ -test, Chuprov coefficient and Wolfe criterion with the amendment of Yates. With the use of nonparametric estimates it was established that at present, the main levers of the state policy should be directed not so much at the economic efficiency but at the development of the potential of each participant in the economy. Nonparametric methodology sufficiently allows us to evaluate the hypothesis of homogeneity and the assertion of independence of the applied anti-inflationary measures for solving social problems facing any state.